Evaluation on antioxidative and neuroprotective activity of bacoside- A, Asiatic acid and kaempferol in endothelin-1 induced cerebral ischemia in rat - Ashutosh Ghosh, Nasima Khanam, Debjani Nath (Journal of Applied Pharmaceutical Science, 2023)
The framework of the present study was mapped out to evaluate the neuroprotective efficacy of bacoside-A, Asiatic acid, and kaempferol as antioxidants in the endothelin-1 (ET-1) induced focal cerebral ischemic brain of rats. Oral administration of bacoside-A (50 mg/kg), Asiatic acid (50 mg/kg), and kaempferol (50 mg/kg) significantly reduced the infarct volume to 31.8% ± 1.30%, 32.3% ± 1.25%, and 34.06% ± 1.30%, respectively, compared to the vehicle–treated ischemic (I/R) group. The neurological deficit was significantly reduced and the neuropathological condition of microglia and astrocytes were also improved. Significant increases in calcium levels and malondialdehyde and reduction (p < 0.01) at the levels of antioxidative enzymes superoxide dismutase, catalase and reduced glutathione were observed. Considering the level of efficacy, Bacoside-A was found to be the most potent neuroprotective antioxidant among the three phytochemicals.
Keywords: Cerebral ischemia, bacoside A, asiatic acid, kaempferol, infarct volume, neuroprotective